Effect of Life Review and Cognitive Therapy on Depression in Patients with Chronic Renal Failure - Sutinah Sutinah (Jurnal Keperawatan Padjadjaran, 2020)
Patients with chronic renal failure suffer higher rates of depression because of psychological stress due to physical and social changes. Efforts to reduce depression level are needed. Cognitive therapy and life review therapy are believed to be effective in reducing depression. The aim of this study was to compare the effects of life review therapy alone and in combination with cognitive therapy on depression in patients with chronic renal failure. This study employed a quasi-experiment with a comparison group design. Fifty-six respondents were selected using a consecutive sampling, which thirty-six were assigned in the experiment and comparison group. Depression was measured using Beck Depression Inventory. Dependent and Independent t-test were used for data analyses. The results revealed that the combination of life review and cognitive therapy had a significant effect (p<.05) in reducing depression compared with the life review therapy alone. The average of depression score decreased in the experiment group from 27.04 (4.71) to 22.29 (4.24). But there was no significant change in the average of depression score in the comparison group from 26.54(4.18) to 26.71 (3.70). This therapy can be used as a complementary medicine to treat patients with chronic renal failure, specifically for those with depression, and it serves as a recommendation for nursing intervention in hemodialysis units.